2023
DOI: 10.1007/s11262-023-01982-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of canine chaphamaparvovirus, canine bufavirus, and canine adenovirus in dogs with diarrhea: First report of novel canine bufavirus in Turkey

Abstract: Viral enteritis is a significant cause of death among dogs younger than 6 months. In this study, the presence of canine chaphamaparvovirus (CaChPV), canine bufavirus (CBuV), and canine adenovirus (CAdV) was investigated in 62 diarrheal dogs previously tested for other viral pathogens (canine parvovirus type 2, canine coronavirus, and canine circovirus). CBuV was detected in two dogs (3.22%) and CaChPV in one dog (1.61%). One dog tested positive for three parvoviruses (CPV-2b, CBuV, and CaChPV). All dogs tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the VP1 sequence, a difference of 13.3–13.5% aa was observed between the Chinese and Italian hedgehog BuVs, likely indicative of host species- or geographical-related patterns. For instance, genetic variability has been identified among human BuVs, classified into three distinct genotypes/serotypes [ 45 , 46 , 65 , 66 ], and among canine BuVs, classified into two genotypes [ 21 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the VP1 sequence, a difference of 13.3–13.5% aa was observed between the Chinese and Italian hedgehog BuVs, likely indicative of host species- or geographical-related patterns. For instance, genetic variability has been identified among human BuVs, classified into three distinct genotypes/serotypes [ 45 , 46 , 65 , 66 ], and among canine BuVs, classified into two genotypes [ 21 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This previous finding also suggested the potential role of CBuV in a contributory cause of respiratory diseases in puppies. 25 Since then, CBuV genomic characterization has been widely studied; 1,4,10,12,22,26,48,53 however, neither evidence nor findings supporting the CBuV tropism in infected cases have been investigated. Here, we report a recurrent outbreak of CBuV infection in multiple colonies of puppies in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…25 During the investigation, the CBuV DNA was commonly identified in stool samples of dogs with and without diarrhea; however, it was only detected in respiratory samples obtained from dogs with respiratory diseases, but not in healthy dogs. To date, the epidemiology of CBuV has been reported in Italy, 10,25 Hungary, 25 China, 22,48 India, 12 Türkiye, 1 and Canada, 4 suggesting its distribution of the virus over multiple continents. Although epidemiological investigations have suggested that CBuV is often found in cases of canine enteritis, 22,25,48 neither descriptions of associated pathologic lesions nor association with diseases has been well defined.…”
mentioning
confidence: 99%
“…Epidemiological and clinical information are required to understand if ChPVs have a role as enteric pathogens in dogs [ 18 , 41 , 151 , 152 ]. Indeed, ChPVs’ DNA has been often detected in dogs in co-infection with other viral pathogens such as CBuV, CAdV [ 153 ], CPV-2, CCoV [ 18 , 151 ] and canine distemper virus (CDV) [ 18 ].…”
Section: Chaphamaparvovirusesmentioning
confidence: 99%